Bioequivalence Study of Two Oral Formulations of Cefadroxil in Healthy Volunteers - Kano, Kazue Eunice; Porta, Valentina; Mori Koono, Eunice Emiko; Schramm, Simone Grigoleto; Reis Serra, Cristina Helena dos (Arzneimittelforschung, 2008)
Two different cefadroxil (CAS 50370-12-2) formulations were evaluated for their relative bioavailability in 24 healthy volunteers who received a single 500 mg oral dose of each preparation. An open, randomized clinical trial designed as a two-period crossover study with a 7-day washout period between doses was employed. Plasma samples for assessments of their cefadroxil concentration by HPLC-UV were obtained over 8 h after administration. Values of 48.94 ± 10.18 µg . h/ml for test, and 48.51 ± 9.02 µg . h/ml for the reference preparation AUC0-t demonstrate a nearly identical extend of drug absorption. Maximum plasma concentration Cmax of 16.04 ± 4.94 µg/ml and 16.01 ± 4.02 µg/ml achieved for the test and reference preparations did not differ significantly. The parametric 90% confidence intervals (CI) of the mean of the difference (test-reference) between log-transformed values of the two formulations were 96.80% to 104.51% and 92.01% to 107.00% for AUC0-t and Cmax, respectively. Since for both AUC0-t or Cmax the 90% CI values are within the interval proposed by the Food and Drug Administration, the test product is bioequivalent to the reference product for both the rate and extent of absorption after single dose administration.
Keywords: Antibiotics; CAS 50370-12-2; Cephalosporins; Cefadroxil, bioequivalence